Developing Michigan Cancer Foundation 7 Cells with Stable Expression of E7 Gene of Human Papillomavirus Type 16 - Faezeh Ghasemi; Sina Rostami; Maryam Sadat Nabavinia; Zahra Meshkat (Iranian Society of Pathology, 2016)
Background: Human papillomavirus (HPV) is responsible for the development of cervical neoplasia.  Infection with human papillomavirus type 16 (HPV-16) is a major risk factor for the development of cervical cancer. The virus encodes three oncoproteins (E5, E6 and E7), of which, the E7 oncoprotein is the major protein involved in cell immortalization and transformation of the infected cells. The aim of the current study was to develop Michigan Cancer Foundation 7 (MCF7) cells, which could stably express E7 protein of HPV type 16. Methods: E7 gene of HPV type 16 was introduced into MCF7 cells by Lipofectamine 2000 reagent and the transfected cells were treated with G418 antibiotic. After antibiotic selection of the transfected cells, stable expression of E7 gene of HPV16 was confirmed by reverse transcriptase polymerase chain reaction (RT-PCR). Results: Antibiotic selections of transfected cells were performed and transfected cells were alive in cytotoxic concentration of the antibiotic. RNA was extracted from transfected cells and E7 gene of HPV16 was amplified by RT-PCR method and a 350-bp band corresponds to E7 was observed. Conclusion: Results confirmed the stable transfection of cells. The stably transfected cells can be used as a useful tool in future studies on HPV16 and cancers caused by this virus.